2022
DOI: 10.1108/josm-06-2021-0238
|View full text |Cite
|
Sign up to set email alerts
|

Programmatic advertising in online retailing: consumer perceptions and future avenues

Abstract: PurposeDigital advertising enables retailers to rely on large volumes of data on consumers and even leverage artificial intelligence (AI) to target consumers online with personalised and context-aware advertisements. One recent example of such advertisements is programmatic advertising (PA), which is facilitated by automatic bidding systems. Given that retailers are expected to increase their use of PA in the future, further insights on the pros and cons of PA are required. This paper aims to enhance the under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
(135 reference statements)
0
4
0
Order By: Relevance
“…They found that AI‐powered chatbots had benefits that improved customer engagement. A strong customer–brand relationship can prompt users to provide positive feedback about their brand preferences, brand loyalty and purchase intentions (Cheng & Jiang, 2021; Ciuchita et al, 2023; Yau et al, 2021). The application of AI and chatbots in the music industry aligns with the findings of Kumar et al (2019).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…They found that AI‐powered chatbots had benefits that improved customer engagement. A strong customer–brand relationship can prompt users to provide positive feedback about their brand preferences, brand loyalty and purchase intentions (Cheng & Jiang, 2021; Ciuchita et al, 2023; Yau et al, 2021). The application of AI and chatbots in the music industry aligns with the findings of Kumar et al (2019).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In "Programmatic advertising in online retailing: consumer perceptions and future avenues", Ciuchita et al (2023) focus on the rise of AI-powered programmatic advertising and examine customer interactions with personalized and context-aware programmatic advertising. Specifically, Ciuchita et al (2023) examined consumers' attitude toward programmatic advertising online and their responses toward the retailers delivering the ads.…”
Section: Technology-driven Personalized Service Communicationsmentioning
confidence: 99%
“…In "Programmatic advertising in online retailing: consumer perceptions and future avenues", Ciuchita et al (2023) focus on the rise of AI-powered programmatic advertising and examine customer interactions with personalized and context-aware programmatic advertising. Specifically, Ciuchita et al (2023) examined consumers' attitude toward programmatic advertising online and their responses toward the retailers delivering the ads. Through a systematic review of extant literature, this paper compares the difference between traditional advertising and programmatic advertising.…”
Section: Technology-driven Personalized Service Communicationsmentioning
confidence: 99%
See 1 more Smart Citation